Effect of aspirin dosage on oxidative stress and platelet reactivity in patients undergoing coronary artery bypass grafting (APRICOT): randomized controlled trial - Aleksandra Gąsecka; Rafał Kaczorowski; Katarzyna Pomykała; Tomasz Kucharski; Magdalena Gajewska; Dominika Siwik; Katarzyna Karoń; Maciej Małyszko; Jaromir Hunia; Jakub Michal Zimodro; Paweł Kowalczyk; Oliwia Zagrocka-Stendel; et al. (Platelets)
Coronary artery bypass grafting (CABG) triggers oxidative stress and platelet activation. High acetylsalicylic acid (ASA) dose might mitigate the transient proinflammatory state. We compared the effect of three ASA dosages on post-CABG platelet reactivity, oxidative stress, and serum CD39 and CD73 levels. Thirty-six consecutive patients undergoing elective off-pump CABG, pre-treated with ASA 1 × 75 mg for ≥7 days, were randomized to continue the prior treatment regimen, switch to ASA 1 × 150 mg, or ASA 2 × 75 mg. Blood was collected on admission, 7 days, 1 month, and 3 months after CABG. Platelet reactivity was assessed using impedance aggregometry. Platelet oxidative stress was measured as platelet mitochondria extracellular oxygen consumption rate and oxidatively damaged whole-blood DNA cleavage. Serum CD39 and CD73 levels were determined using ELISA. Platelet reactivity and oxidative stress parameters were comparable in all groups. Patients treated with ASA 2 × 75 mg had higher CD39 levels at 7 days and 1 month (p = .049, p = .033), compared to the control group. ASA 2 × 75 mg was associated a beneficial effect on serum CD39 levels after off-pump CABG, without a significant effect on oxidative stress parameters.